(untitled) (Journal of Solar Energy Research Updates, 2025)
In this paper, a concentrating photovoltaic and temperature difference combined power generation device is designed. The device is guided by the problem of low power generation efficiency of solar cells at high temperature, and transfers the heat of photovoltaic cells to thermoelectric cells to achieve secondary power generation. The research takes the cold end of the thermoelectric battery as the entry point, and studies its influence on the device by controlling the flow rate and temperature of the cooling liquid in the water-cooled radiator. The results show that when the flow rate is 0.5L/min 2.5L/min, the photovoltaic current increases linearly and then increases nonlinearly, while the photovoltaic voltage decreases linearly and then increases nonlinearly. When the water temperature increases from 15°C to 27°C, the photovoltaic current, photovoltaic voltage and thermoelectric voltage decrease with the increase of water temperature, while the thermoelectric current increases with the increase of water temperature. Therefore, selecting the appropriate flow rate and water temperature can further improve the power generation efficiency and performance of the system.